Peninjauan dan Pengukuran Eksisting Bangunan Gereja HKBP Ressort Perumnas Klender - Grace Putri Dianty; Candra Christianti Purnomo; Sally Septania Napitupulu; Sudarno P Tampubolon (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2022)
Planning/ design of a mature structure is very important in constructing a building. This is one of the goals of the Faculty of Engineering Community Service (PKM) held at the HKBP Resort Church of Perumnas Klender. The activities carried out are measuring and depicting existing church buildings that have stood, where these images can be used by the Church for the development and improvement of the Church in the future. The method used in this PKM is to conduct a field survey to be able to prepare measurements of the church building, then take measurements and draw the initial sketch of the church building on the first and second floors as a whole, until at the end of the activity a 2-dimensional drawing of the church building is carried out according to the measurements that have been made. in the field. This PKM activity produces two-floor dimensional plan builds analyzed by architectural and civil perspectives. Keywords: measurement and drawing; church building, Klender housing estate.